MOTIVATIONAL STRATEGIES IN SPEAKING FOR THE 4TH AND 5TH GRADERS IN LOWER MOVER CLASSES AT FOREIGN LANGUAGE CENTER A, HANOI - Tăng, Thị Quỳnh Thơ (2021)
The research aims at exploring motivational strategies used by teachers at center A in speaking lessons for the 4th and 5th graders in Lower Mover classes. In addition, pedagogical implications for speaking lessons for young learners can be drawn from this research. To achieve these goals, the research attempts to answer the following questions: What are the motivational strategies that teachers often use in teaching speaking and the frequency of utilized strategies? What kind (s) of motivational strategies motivate(s) 4th and 5th graders most as perceived by learners themselves?